Cultural capital and university dropout in Saudi Arabia: A qualitative case study of students withdrawing from university Education - Nahedh Salem Aloudah. Abied Abdullah Alamri . Nasser Ahmed Almusalam (Journal of Daoist Studies, 2026)
This study explored the role of cultural capital in student dropout at several Saudi universities, drawing on Bourdieu’s theory. A qualitative case study approach was employed, with data collected through open-ended interviews and simple observation. The sample comprised 10 participants from two public universities. The results identified eight common factors contributing to university dropout, grouped into three main themes: factors related to the initial adaptation phase, those associated with academic and social integration, and those regarding the actual withdrawal phase. Specifically, the findings highlighted poor language skills and previously acquired academic habits, limited freedom and guidance in choosing a major, low parental educational and cultural levels, ineffective academic advising, symbolic violence by some faculty members, weak peer interaction and social integration, academic failure linked to lack of parental monitoring, and limited access to academic resources due to low family economic status as the most significant contributors to dropout. The researchers provided several recommendations for enhancing students’ cultural capital and reducing university dropout.